Durability Assessment of SOFC Stacks with Several Types of Structures for Thermal Cycles during Their Lifetimes on Residential Use. (2nd June 2015) - Hatae, Toru; Sato, Koki; Somekawa, Takaaki; Matsuzaki, Yoshio; Amaha, Shinji; Yoshikawa, Masahiro; Mugikura, Yoshihiro; Miyara, Kengo; Oshima, Toshihiro; Taniguchi, Shunsuke; Sasaki, Kazunari; Shimazu, Megumi; et al.
Abstract : We have been developing a rapid evaluation method for durability of SOFC stacks for thermal cycles during their lifetimes based on the assumption of residential use. The durability for thermal cycles is expected to be affected by the degradation during their long-term operation. In order to accelerate the evaluation, some treatments to intentionally cause the degradation were investigated. A degradation factor was determined depending on the SOFC stacks with different structures respectively because each degradation mechanism during their long-term operation also depends on them. The SOFC stacks were supplied by four SOFC stack manufactures in Japan. In this work, we investigated the Cr poisoning treatment to tubular SOFC (TOTO) and the S poisoning treatment to single step co-fired planar SOFC (Murata Manufacturing). As results of both cases, 10 years' worth of degradation was successful to be intentionally caused in short period.